Breviscapine promotes functional recovery in rats with traumatic brain injury associated with netrin‐1 upregulation. Issue 3 (28th September 2017) - Zhang, Lang‐Chun; Dan, Qi‐Qin; Zou, Yu; Xia, Qing‐Jie; Yuan, Hao
Abstract : Objective: Traumatic brain injury (TBI) usually induces cognitive impairments, including motor and neuropsychiatric deficits. Breviscapine shows broad pharmacological effects and facilitates functional recovery from cardiovascular and cerebrovascular insults, such as brain ischemia and myocardial ischemia. However, the role of Breviscapine in TBI remains vague. In this study, we investigated whether Breviscapine can improve functional deficits in rats with TBI, and explained the associated molecular mechnism. Method: Thirty adult female Sprague–Dawley (SD) rats were randomly divided into three groups: sham group, TBI group, Breviscapine treatment group (Breviscapine + TBI). TBI was initiated using an electromagnetic‐controlled cortical impact device. Breviscapine (0.375 mg/kg) were administrated into lateral ventricles one time after TBI induction. Behavioral evaluation was conducted after TBI by mNSS tests. Western blotting analysis, immunofluorescent staining and Quantitative real‐time polymerase chain reaction were performed to evaluate the protein and mRNA level of Netrin‐1 in the brain tissues, respectively. Results: Compared with the sham rats, TBI group had a deteriorated behavioral function at 2 days, 6 days, 10 days and 14 days post TBI. However, Breviscapine administration showed a neurobehavioral improvement compared with TBI group at day 10 and day 14 after TBI, in addition, the levels was decreased in TBI rats compared with the sham group while Breviscapine treatment upregulated the expression of Netrin‐1. Conclusion: Breviscapine can improve neurological function in rats with TBI and the mechanism is probably associated with Netrin‐1 upregulation. The current study therefor provides a potential therapeutical drug for therapy of TBI and underlying mechanism is involved in Netrin‐1.